Transition from Intravenous Epoprostenol to Oral or Subcutaneous Therapy in Pulmonary Arterial Hypertension: A Retrospective Case Series and Systematic Literature Review - Kirily Park; David Ostrow; Robert D Levy; John Swiston (Canadian Respiratory Journal)
BACKGROUND: Intravenous epoprostenol, a prostaglandin analogue, has been a mainstay of therapy for patients with advanced pulmonary arterial hypertension (PAH) since the early 1990s. This medication has multiple side effects, and sudden discontinuation is potentially associated with severe sequelae. Several recent case series have described the transition from intravenous to newer oral or subcutaneous therapies. A case series detailing the authors’ experience with such transitions, and a systematic lierature review is presented.